Clinical utility of DaTscan™ imaging in the evaluation of patients with parkinsonism: a US perspective. (4th March 2017) - Isaacson, Stuart H.; Fisher, Stanley; Gupta, Fiona; Hermanowicz, Neal; Kremens, Daniel E.; Lew, Mark F.; Marek, Kenneth; Pahwa, Rajesh; Russell, David S.; Seibyl, John
ABSTRACT: Introduction: Single photon emission computed tomography (SPECT) with Ioflupane I123 injection (DaTscan™) was approved by the Food and Drug Administration in 2011 for striatal dopamine transporter visualization to assist in the evaluation of adult patients with suspected parkinsonian syndromes. While brain SPECT imaging using DaTscan is a covered service under Medicare policy, there is a lack of consensus on its role in routine clinical practice in the US. Areas covered: To address this issue, an expert group of US-based movement disorders neurologists convened to discuss the clinical utility of DaTscan in movement disorders practices within the US. The group identified and discussed routine clinical scenarios where imaging with DaTscan can provide useful information that may impact management and/or clarify clinical diagnoses. This paper summarizes a consensus reached by the expert group at this meeting. Expert commentary: The major utility of DaTscan imaging is the assistance it provides in distinguishing between nigrostriatal dopaminergic degeneration and non-nigrostriatal degeneration in patients displaying equivocal signs and symptoms of parkinsonism.